Building Political Awareness of Generation Z in Medan City: Political Literacy as a Fortress against Radicalism and Identity Politics - Annisa Pratiwi Surianto; Mardian Idris Harahap; Junaidi Junaidi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to analyze the level of political literacy and the views of Generation Z in Medan City on the issues of identity politics and radicalism. The method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show that the majority of Generation Z has limited political understanding and tends to follow the flow of public opinion, especially through social media. Although they generally reject the practice of identity politics and radicalism, this rejection is more emotional than based on deep conceptual understanding. The low level of political literacy and critical awareness is a challenge in forming a participatory and democratically resilient young generation. Therefore, increasing political literacy, anti-radicalism education, and understanding of diversity need to be instilled through formal education, digital literacy campaigns, and strengthening national values. This study recommends multi-sector collaboration to build a Generation Z that is politically aware, inclusive, and resilient to extreme ideologies